RELAÇÃO ENTRE A VARIABILIDADE CLIMÁTICA E A PRODUTIVIDADE DE BATATA EM GUARAPUAVA - PARANÁ - Bereze, Juliane (2016)
The variability of rainfall determines dry and rainy seasons that influence agriculture in different regions of the country, as well as on a local scale. The main known source of interannual climate variability is the phenomenon called El Niño - Southern Oscillation (ENOS), which causes anomalies in atmospheric circulation on a global scale, and extreme weather anomalies are related to the phases: warm (El Niño) and cold (La Niña) ENOS. This paper presents a study of the relationship between climate and potato agricultural productivity in Guarapuava-PR, using time series for the period 1990-2013 precipitation and Southern Oscillation Index (IOS) and aims to study the culture of behavior potato, as well as influence of precipitation on them. We calculated simple correlations between rainfall and agricultural productivity has been found that the precipitation directly affected the potato yield. In addition, the impacts were analyzed caused by ENOS on rainfall and crop productivity during the study it became clear that 24, 6 events correlated with precipitation of Guarapuava. In the analysis carried out in the potato harvest periods is clear correlation between TSM and precipitation for the period studied, totaling more than 58% of events related to precipitation.